Changes in Mucin Production in Human Airway Epithelial Cells After Exposure to Electronic Cigarette Vapor With or Without Nicotine - Song, Si-Youn; Kwak, So Young; Choi, Yoon Seok; Bae, Chang Hoon; Kim, Yong-Dae (Clinical and experimental otorhinolaryngology, 2021)
Objectives. The emergence of electronic cigarettes (e-cigarettes) has created new perceptions of the tobacco market. Unlike traditional tobacco, the greatest advantage of e-cigarettes is that they have less smell and are convenient and inexpensive. Most e-cigarette smokers believe that e-cigarette smoking is less harmful than traditional smoking. Information on the effects of e-cigarettes on human health is limited, and the issue remains controversial.Methods. We studied the effects of e-cigarette vapor on mucin (MUC5AC and MUC5B) and the change of MUC5AC and MUC5B from e-cigarette liquid with or without nicotine in respiratory epithelial cells. The effects of e-cigarette vapor with or without nicotine on mucin, along with the involved signaling pathways, were investigated using reverse transcriptase-polymerase chain reaction (PCR), real-time PCR, enzyme immunoassays, and immunoblot analysis with several specific inhibitors and small interfering RNA.Results. E-cigarette vapor with or without nicotine stimulated MUC5AC, but not MUC5B, expression in respiratory epithelial cells. In addition, we showed that e-cigarette vapor with and without nicotine induced MUC5AC expression via activation of the mitogen-activated protein kinase (MAPK; extracellular signal-regulated kinase [ERK] 1/2 and p38) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) signaling pathways in human airway epithelial cells.Conclusion. E-cigarette vapor with and with nicotine significantly increased MUC5AC expression in human airway epithelial cells.